2019
DOI: 10.3144/expresspolymlett.2019.52
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of isophorondiamine based epoxy hardeners from aminolysis of PET

Abstract: The solvolysis of poly(ethylene-terephthalate) (PET) is one of the most researched areas in chemical recycling. In this study PET aminolysis with isophorondiamine has been done -in opposition to recent trends -without excess reagent and the raw reaction product was further used without purification. The aminolysis product was thoroughly characterized with nuclear magnetic resonance (NMR) spectroscopy. Isophoronediamine was used as a solvent to prepare amine crosslinker solutions for epoxy resins. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The accelerative nature of the EG side product and the terephthalamide diamine main products during the epoxy curing reaction was observed 66 …”
Section: Chemical Recycling Of Petmentioning
confidence: 97%
See 1 more Smart Citation
“…The accelerative nature of the EG side product and the terephthalamide diamine main products during the epoxy curing reaction was observed 66 …”
Section: Chemical Recycling Of Petmentioning
confidence: 97%
“…59 Fukushima et al carried out organocatalytic aminolysis using The accelerative nature of the EG side product and the terephthalamide diamine main products during the epoxy curing reaction was observed. 66 Meawad and Ibrahim conducted a study to develop a novel bifunctional cement dispersing agent via aminolysis depolymerization of PET waste with 4-amino-1-butanol in the presence of sodium acetate as a catalyst, which contributed to fluidity modification of fresh cement. 67 In this regard, PET waste was subjected to aminolysis using excess EA in the presence of different inexpensive nontoxic catalysts, including sodium acetate, sodium bicarbonate, and sodium sulphate.…”
Section: Aminolysismentioning
confidence: 99%
“…Aminolysis of PET yields diamides or amido amine of terephthalic acid that are produced by several techniques and can be used as curing agents for epoxy resins [22]. PET aminolysis products as epoxy curing agents is still an expanding area that reported few works have been focused to apply as epoxy organic coatings [27,28]. It was previously reported that the aminolysis of PET with cycloaliphatic amines is advantageous in modifying slower curing for epoxy systems [27].…”
Section: Introductionmentioning
confidence: 99%
“…PET aminolysis products as epoxy curing agents is still an expanding area that reported few works have been focused to apply as epoxy organic coatings [27,28]. It was previously reported that the aminolysis of PET with cycloaliphatic amines is advantageous in modifying slower curing for epoxy systems [27]. In this respect, the present work aims to produce for the first time polyamine amide imidazolium acetate ionic liquid (PAIIL) from aminolysis of PET waste with pentaethylenehexamine (PEHA) to alleviate the environmental pollution from PET waste.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the goal of the solvolysis the reaction parameters can be tailored to produce BHET or oligomers that could be further used in new reactions [5,18,[37][38][39][40][41][42][43]. Usually, oligomers are discarded during the purification processes, only a few studies used these or the raw solvolysis product [44][45][46][47][48]. In most of the cases, the purpose of glycolysis is the reproduction PET via BHET.…”
Section: Introductionmentioning
confidence: 99%